2021
DOI: 10.1002/cplu.202100089
|View full text |Cite
|
Sign up to set email alerts
|

A Hypervalent Cyclic Dibenzoiodolium Salt as a Halogen‐Bond‐Donor Catalyst for the [4+2] Cycloaddition of 2‐Alkenylindoles

Abstract: A stable, hypervalent cyclic dibenzoiodolium salt acted as a strong halogen bonding (XB)-donor catalyst for [4 + 2] cycloaddition of 2-alkenylindoles, and not as an oxidizing agent. The cross-[4 + 2] cycloaddition of 2-vinylindoles with 2-alkenylindoles was catalyzed smoothly by the hypervalent cyclic dibenzoiodolium triflate catalyst to give the tetrahydrocarbazoles in up to 99 % yield with 17 : 1 diastereoselectivity. The hypervalent cyclic dibenzoiodolium salt was also applicable to the Povarov reaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 65 publications
0
24
0
2
Order By: Relevance
“…Among the XB donor species, the iodine derivatives are shown to exhibit the highest catalytic activity. Although search for new uncharged iodine-containing XB-donating species is going on, it has been clearly demonstrated that noncovalent organocatalysts based on cationic iodine­(I) , and iodine­(III) derivatives exhibit the highest catalytic activity (Figure A−C).…”
Section: Introductionmentioning
confidence: 99%
“…Among the XB donor species, the iodine derivatives are shown to exhibit the highest catalytic activity. Although search for new uncharged iodine-containing XB-donating species is going on, it has been clearly demonstrated that noncovalent organocatalysts based on cationic iodine­(I) , and iodine­(III) derivatives exhibit the highest catalytic activity (Figure A−C).…”
Section: Introductionmentioning
confidence: 99%
“…For XB donors, it has been demonstrated that cationic iodine(I)-containing species C-in particular, iodoazoliums [30][31][32][33][34][35][36][37][38][39] -effectively catalyze an extensive series of organic transformations, whereas hypervalent iodine(III) derivatives F (i.e., diaryliodonium salts) featuring two σ-holes at the iodine atom possess a greater catalytic activity than azolium-based iodine(I) species. [40][41][42][43][44][45][46][47][48][49][50][51] It is worth mentioning that diarylbromonium salts (F; X = Br) have also been reported to exhibit high catalytic activity. [52][53][54][55] Organocatalysts based on ChB donors have gained increasing attention over the last five years.…”
Section: Introductionmentioning
confidence: 99%
“…, diaryliodonium salts) featuring two σ-holes at the iodine atom possess a greater catalytic activity than azolium-based iodine( i ) species. 40–51 It is worth mentioning that diarylbromonium salts ( F ; X = Br) have also been reported to exhibit high catalytic activity. 52–55…”
Section: Introductionmentioning
confidence: 99%
“…Diaryliodonium cations (Ar 2 I + ) are multipurpose reagents in organic synthesis. They have received major attention as arylating agents but attracted interest also as topochemical reagents and noncovalent catalysts. Their ability to form attractive interaction was recognized long ago, when Alcock introduced the concept of secondary bonding . After the rationalization of these interactions as charge-assisted halogen bonds (HaBs), the use of diaryliodonium cations as tectons in crystal engineering became more and more common. , This increased interest was favored by the unique geometric features of these HaB donors with respect to other organic tectons.…”
Section: Introductionmentioning
confidence: 99%